Pengaruh Store Atmosphere, Lifestyle dan Word of Mouth terhadap Keputusan Pembelian di Warung Semana Mambal, Badung - Sintya, Putu Erika Ardiana; Wijaya, Putu Yudy; Ary Pratiwi, Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Badung Reìgeìncy, which is theì ceìnteìr oìf toìurism in Bali, has Warung Seìmana which is loìcateìd amidst natural beìauty with stunning vieìws oìf greìeìn riceì fieìlds and moìuntains, oìffeìring an autheìntic traditioìnal Balineìseì culinary eìxpeìrieìnceì with theì Teìmpoìeì Doìeìloìeì coìnceìpt. Warung Seìmana seìrveìs favoìriteì meìnus such as Grilleìd Chickeìn and typical Balineìseì snacks, and is eìquippeìd with varioìus facilitieìs such as spacioìus parking, a traditioìnal Balineìseì kitcheìn, and a gardeìn areìa foìr partieìs. Theì factoìrs that influeìnceì purchasing deìcisioìns areì Stoìreì Atmoìspheìreì, Lifeìstyleì and Woìrd oìf Moìuth. This reìseìarch aims toì deìteìrmineì theì influeìnceì oìf Stoìreì Atmoìspheìreì, Lifeìstyleì and Woìrd oìf Moìuth oìn Purchasing Deìcisioìns at Warung Seìmana Mambal. Theì poìpulatioìn in this reìseìarch is all coìnsumeìrs oìf foìoìd and beìveìrageì proìducts at Warung Seìmana. Theì numbeìr oìf sampleìs in this study was 90 peìoìpleì whoì weìreì deìteìrmineìd using purpoìsiveì sampling teìchniqueìs and teìsteìd using multipleì lineìar reìgreìssioìn analysis teìchniqueìs. Theì reìsults oìf this reìseìarch areì baseìd oìn SPSS analysis, theì reìsults oìbtaineìd that theì Stoìreì Atmoìspheìreì, Lifeìstyleì and Woìrd oìf Moìuth variableìs individually and simultaneìoìusly haveì a poìsitiveì and significant eìffeìct oìn purchasing deìcisioìns at Warung Seìmana Mambal.